EFEKTIFITAS PENELUSURAN INFORMASI APLIKASI SIPUSPA (CERIA) DI PERPUSTAKAAN UNIVERSITAS PGRI PALEMBANG - Azizah, Ngalia Nur (DE FACTO : Journal Of International Multidisciplinary Science, 2023)
Searching for information is a necessity of life that is used to plan, take action and do what is needed to gain an understanding that is acceptable to reason. The purpose of information retrieval activities is to obtain information needed by researchers, library users, policy makers and other users from within a collection of library materials or from a particular information storage system. With the existence of information retrieval tools, it is hoped that the process of searching for information can be carried out more quickly and more specifically. These tools can be automated systems or software, for example, such as Sipuspa (Ceria), to prove whether the software really makes it easier for users to search and is highly utilized by users, of course, it is necessary to conduct an effectiveness test. In this research, we will discuss the effectiveness of the software used at the Palembang PGRI University Library, namely Sipuspa (Ceria) as a means of information retrieval. Data collection methods used were observation and interviews. In this study, the authors used descriptive data analysis, namely describing an object being discussed.